Node clustered deployment of emergency Internet of things based on UAV with equipment access restriction - Wei WANG; Yajing LIANG; Li PENG; Zhongcheng WEI; Jijun ZHAO (物联网学报)
Lack of ground base station in emergency Internet of things for public security application scenarios, the unmanned aerial vehicle (UAV) as the air-based base station was adopted to solve the problem of node cluster deployment under the condition of limited access of emergency Internet of things ground terminal equipment.A clustering deployment method based on on-demand K-means (ODKM) was proposed.Firstly, base station selection and equipment clustering were carried out according to the equipment access ability of different UAV air-based base stations through two clustering steps.Secondly, by solving a relaxed non convex nonlinear optimization model, the UAV air-based base station deployment based on energy efficiency optimization was realized.The experimental results show that the proposed method can meet the constraints of UAV base station access ability, and has a good performance in balancing the transmission energy consumption of each cluster, and realizes the goal of communication energy saving when the ground terminal equipment needs to access.